(untitled) (Agroindustria, Sociedad y Ambiente, 2021)
In this paper, the process automation trite coffee was realized, the research is framed in the form of practicable project and other development in the next stages, diagnosis, feasibility study and design, which is the main objective, due a damage suffer health level persons responsible for work in process trite coffee manually working them. The project is based on building a machine that can thresh parchment coffee in a short time UN, initially comprises a hopper where the parchment was deposited which is moved to the hopper of the threshing through the United Nations endless screw. Said hopper will feature sensors level gauges which at perceiving signal will turn on and off motors worm. For the worm 110v AC motors were used as for the process trite. The whole process was carried out through a control module commanded by a 16F877 PIC microcontroller, in addition to other more basic electronic components such as transistors, relays, integrated, among others. Achieving a mechatronic design capable of automating the coffee threshing system